Do chronic myeloid leukemia patients with late "warning" responses benefit from "watch and wait" or switching therapy to a second generation tyrosine kinase inhibitor?. Issue 11 (27th August 2014) - García‐Gutiérrez, Valentin; Puerta, Jose Manuel; Maestro, Begoña; Casado Montero, Luis Felipe; Muriel, Alfonso; Molina Hurtado, Jose Ramon; Perez‐Encinas, Manuel; Moreno Romero, Maria Victoria; Suñol, Pere Barba; Sola Garcia, Ricardo; De Paz, Raquel; Ramirez Sanchez, Maria Jose; et al.
<x xml:space="preserve">Abstract</x> In the latest recommendations for the management of chronic‐phase chronic myeloid leukemia suboptimal responses have been reclassified as "warning responses." In contrast to previous recommendations current guidance advises close monitoring without changing therapy. We have identified 198 patients treated with first‐line imatinib, with a warning response after 12 months of treatment (patients with a complete cytogenetic response but no major molecular response [MMR]). One hundred and forty‐six patients remained on imatinib, while 52 patients changed treatment to a second generation tyrosine kinase inhibitor (2GTKI). Changing therapy did not correlate with an increase in overall survival or progression‐free survival. Nevertheless, a significant improvement was observed in the probability of a MMR: 24% vs. 42% by 12 months and 43% vs. 64% by 24 months (P = 0.002); as well as the probability of achieving a deep molecular responses (MR4.5): 1% vs. 17% and 7% vs. 23% by 12 and 24 months, respectively (P = <0.001) .The treatment change to 2GTKI remained safe; however, we have observed a 19% of treatment discontinuation due to side effects. We have observed an improvement of molecular responses after changing treatment to 2GTKI in patients with late suboptimal response treated with imatinib first line. However, these benefits were not correlated with an improvement of progression free survival or overall survival. Am. J. Hematol. 89:E206–E211, 2014. © 2014 Wiley Periodicals, Inc.